Efeitos do reforçamento negativo sobre a recorrência de culturantes em microculturas de laboratório - ALVES, Luiz Felipe Costa (Universidade Federal do Pará, 2019)
Behavior Analysis has advanced in the study of metacontingency relations to explain cultural phenomena. Despite the frequent use of aversive control in everyday cultural practices, data from the few analytic-behavioral studies that address the cultural phenomena in the laboratory and their relationship to aversive stimulation are still preliminary and inconsistent. Studies that seek to verify relations between cultural phenomena and aversive control, using experimental metacontingency analogues, can be valuable for the consolidation of this field of research and for the understanding of important portions of real social relations. In this sense, the present study had as objective to verify the effects of the application of negative reinforcement on the recurrence of culturantes in microcultures of laboratory. Two laboratory microcultures of 3 participants were exposed to an ABAB and BABA design, respectively. The task consisted of line choices in a 10x10 matrix, with colored lines numbered from 1 to 10. The choice of odd rows throughout the procedure produced an individual token (individual consequence) exchangeable for money, and the target culturant was the choice of different colored lines, which avoided the loss of tokens equivalent to school items to be donated to a public school (cultural consequence). The data suggest the selection of a culturante as a result of a negative reinforcement procedure. In addition, the two microcultures were affected in different ways by contacting the metacontingency. One had the production of individual consequences reduced after contacting the metacontingency, and the other maintained the production of individual consequences throughout the experimental session. This variation may indicate the possibility of elaborating a procedure in which to measure independent individual responses in a study of cultural phenomena becomes unnecessary. Although the literature points to a possible difference in the effect of positive and negative reinforcement on culturist selection, no evidence was found in the present study. However, since the present study dealt only with culturant selection, it is suggested to use the current procedure as the initial stage of studies that seek to explore culturant transmission using a cultural negative reinforcement analogue.